What Matters in Online Speaking Classrooms?: Practical Implications - Ramadhani, Dwiansari; Kayla Artamevia Putri (English Department, Universitas Negeri Surabaya, 2024)
This paper aims to propose practical implications of designing online speaking classrooms by presenting several issues and key aspects that need to be reevaluated by teachers or course designers. Several studies regarding factors motivating and hindering students’ speaking performance in online modes have been conducted but they do not discuss the interrelationship between each factor. Drawing from previous references, the study breaks down certain conditions that should be fulfilled if students’ positive attitudes and improved performance in online speaking classrooms should be achieved. Those conditions are related to the learning activities developed by the teacher, the choice of learning platforms, the exposure to inputs and resources, and the teacher’s preparedness for technology operation. At the end of this article, practical solutions are proposed to manage related issues and hence recommend suggestions for speaking teachers to improve more effective online classroom activities accordingly. I believe when designed effectively, online speaking classrooms can be one solution's alternative to facilitate practice regardless of learners’ education level and occupation.